A generalized reduced fluid dynamic model for flow fields and electrodes in redox flow batteries. Issue 4 (24th January 2022) - Cheng, Ziqiang; Tenny, Kevin M.; Pizzolato, Alberto; Forner‐Cuenca, Antoni; Verda, Vittorio; Chiang, Yet‐Ming; Brushett, Fikile R.; Behrou, Reza
Abstract: High‐dimensional models typically require a large computational overhead for multiphysics applications, which hamper their use for broad‐sweeping domain interrogation. Herein, we develop a modeling framework to capture the through‐plane fluid dynamic response of electrodes and flow fields in a redox flow cell, generating a computationally inexpensive two‐dimensional (2D) model. We leverage a depth‐averaging approach that also accounts for variations in out‐of‐plane fluid motion and departures from Darcy's law that arise from averaging across three‐dimensions (3D). Our resulting depth‐averaged 2D model successfully predicts the fluid dynamic response of arbitrary in‐plane flow field geometries, with discrepancies of <5% for both maximum velocity and pressure drop. This corresponds to reduced computational expense, as compared to 3D representations (<1% of duration and 10% of RAM usage), providing a platform to screen and optimize a diverse set of cell geometries.